Validation of a piston type wave-maker using Numerical Wave Tank. (1st February 2017) - Prasad, Deepak Divashkar; Ahmed, Mohammed Rafiuddin; Lee, Young-Ho; Sharma, Rajnish N.
Abstract: Commercial Computational Fluid Dynamics (CFD) code ANSYS – CFX which solves the Reynolds Averaged Navier-Stokes Equations (RANSE) is used to simulate waves in a 3D Numerical Wave Tank (NWT). The free surface is captured using Volume of Fluid (VOF) method. The numerical code to generate waves in NWT is first validated against experimental data to check the accuracy and robustness of the code. The experimental setup included a turbine and as such the initial numerical code was validated by comparing the wave height and the performance of the turbine against the experimental data. The initial numerical results show good agreement with the experimental data. Later an actual NWT is constructed to generate desired wave climate based on field measurements at a site in Fiji. The CFD results show very good agreement with field measured wave height of 1.23 m and field measured wave power of 9.81 kW/m. The CFD results were also verified with analytical solutions. The difference in the results is within 3% highlighting the validity of the CFD code which can further be extended to investigate other phenomena. Highlights: Waves are simulated in a Numerical Wave Tank (NWT). Desired wave climate based on actual measurements is created. The results of Computational Fluid Dynamics (CFD) simulation showed good agreement with experimental data. CFD results obtained using NWT showed good agreement with theoretical models. CFD results also matched with the field data proving that NWT can be used for good predictions.